2016
DOI: 10.1016/j.apenergy.2016.08.153
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of methane production from bituminous coal through biogasification

Abstract: To optimize methane production from bituminous coal through use of a well-studied microbial community derived from the same Illinois basin in USA, a total of 12 parameters were first evaluated by setting up 64 reactors following a 2-level factorial design. Among the 12 parameters, temperature, coal loading, particle size and ethanol were found to have statistically significant effects on methane content and yield from coal. Following screening, to identify optimal value for each significant factor, a Box-Behnk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 26 publications
2
36
0
Order By: Relevance
“…To study the mechanisms involved in coal bioconversion, a majority of research has been performed in a laboratory environment where in situ temperature and/or pressure may be simulated in a batch process. As reported by different researchers [9,[17][18][19][20][21][22][23][24], a common phenomenon has been observed: methane production (mass of methane per mass of coal) peaked and then either slowed down or stopped increasing after certain period of time. The possible explanations could be: 1) exhaustion of nutrients in the medium and coal used; 2) product inhibition: CH 4 , H 2 S and NH 3 in the headspace may inhibit microbial activities; 3) accumulation of toxic or inhibitory degradation products; and 4) the residual coal was not available to microbial cells [19].…”
Section: Introductionmentioning
confidence: 80%
See 4 more Smart Citations
“…To study the mechanisms involved in coal bioconversion, a majority of research has been performed in a laboratory environment where in situ temperature and/or pressure may be simulated in a batch process. As reported by different researchers [9,[17][18][19][20][21][22][23][24], a common phenomenon has been observed: methane production (mass of methane per mass of coal) peaked and then either slowed down or stopped increasing after certain period of time. The possible explanations could be: 1) exhaustion of nutrients in the medium and coal used; 2) product inhibition: CH 4 , H 2 S and NH 3 in the headspace may inhibit microbial activities; 3) accumulation of toxic or inhibitory degradation products; and 4) the residual coal was not available to microbial cells [19].…”
Section: Introductionmentioning
confidence: 80%
“…In this study, the coal loading used was 20.2% (w/v) which was much higher than others reported. This loading was obtained through an optimization study [17] and toxicity from coal at this high content has not been observed for the microbial community used here. Results from the Group 1 reactors also revealed that coal was not the rate-limiting substrate.…”
Section: Methane Contentmentioning
confidence: 98%
See 3 more Smart Citations